2012
DOI: 10.1186/1756-0500-5-226
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety education at Japanese medical schools: results of a nationwide survey

Abstract: BackgroundPatient safety education, including error prevention strategies and management of adverse events, has become a topic of worldwide concern. The importance of the patient safety is also recognized in Japan following two serious medical accidents in 1999. Furthermore, educational curriculum guideline revisions in 2008 by relevant the Ministry of Education includes patient safety as part of the core medical curriculum. However, little is known about the patient safety education in Japanese medical school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…Since the Patient Safety Act was implemented in 2016 in Korea, there has been an increasing need to incorporate patient safety principles in medical education, including at the undergraduate level [ 8 ]. Some medical schools in other countries have implemented patient safety curricula [ 28 30 ]. In Korea, however, a patient safety medical curriculum has not been actively discussed by medical educators [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the Patient Safety Act was implemented in 2016 in Korea, there has been an increasing need to incorporate patient safety principles in medical education, including at the undergraduate level [ 8 ]. Some medical schools in other countries have implemented patient safety curricula [ 28 30 ]. In Korea, however, a patient safety medical curriculum has not been actively discussed by medical educators [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, risk management has many components including learning and education from adverse incidents. A Japanese study showed that the time devoted to patient safety education is four hours or less [56].…”
Section: Patients' Perspective On Lack Of Trust and Involvement As Wmentioning
confidence: 99%
“…In addition, they are eager to acquire new skills and being in an academic setting also provides the environment where thinking with an "open mind" is possible. Although there is more and more attention on patient safety in the medical curricula, the amount of time given to the topic is likely to be insufficient [11][12][13][14][15]. Greater emphasis needs to be placed on training in these areas in the curricula of medical, pharmacy, and nursing schools [16].…”
Section: Introductionmentioning
confidence: 97%